An updated checklist of Thyatirinae (Lepidoptera, Drepanidae) from China, with descriptions of one new species - Jiang, Nan; Yang, Chao; Xue, Dayong; Han, Hongxiang (Zootaxa, 2015)
A total of three tribes, 38 genera and 148 species of Thyatirinae from China are listed together with one dubious record. Of these, one new species, Stenopsestis bruna sp. nov., is described. Macrothyatira danieli Werny, 1966, stat. rev., is restored to specific rank. Cymatophora subampliata Houlbert, 1921, is downgraded to subspecific rank as Tethea (Tethea) albicostata subampliata (Houlbert, 1921), stat. nov. Two genera, four species and three subspecies are recorded for the first time from China (Chiropsestis Laszlo, Ronkay & Ronkay, 2001, Hiroshia Laszlo, Ronkay & Ronkay, 2001, Chiropsestis rubrocinerea Laszlo, Ronkay & Ronkay, 2001, Hiroshia albinigra Laszlo, Ronkay & Ronkay, 2001, Parapsestis hausmanni Laszlo, Ronkay, Ronkay & Witt, 2007, Spica luteola Swinhoe, 1889, Parapsestis cinerea pacifica Laszlo, Ronkay, Ronkay & Witt, 2007, Tethea (Saronaga) consimilis aurisigna Bryk, 1943, Nothoploca nigripunctata fansipana Laszlo, Ronkay & Ronkay, 2001). Ten misidentifications in Zhao (2004) are corrected. Illustrations of external features and genitalia of the new taxa and new records are presented.